Description and molecular characterization of a new species of tarantula, pamphobeteus verdolaga, from colombia (Araneae: Mygalomorphae: Theraphosidae) (2023)
A new species of Pamphobeteus Pocock, 1901 is described from the Colombian Andes, Medellín, Antioquia. The biochemistry and molecular characteristics of the venom of this new species (previously identified as Pamphobeteus aff. nigricolor) has been alrea.